Professional Certification and Motivation toward Lecturer Performance in Bekasi, Indonesia - et. al., Dhian Tyas Untari, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study is to analyze the effect of certification and Motivation to improving lecturer performance, both partially and simultaneously. This research involved 37 lecturers who taught at the University located in Bekasi. The research was conducted by distributing research instruments through Google forms in several Lecturer Associations. The analytical method used is multiple regression, testing the closeness of the relationship between variables with correlation analysis and testing the hypothesis with the t test and F test. The results of the study show that, certification significantly and motivation can significanly improve the lecturer performance. The results of this study can be a refferences for stakeholders both the University and the Ministry and Lecturer Associations to more focus in increasing appreciation for the achievement of lecturers' performance and Motivation.